A Qualitative Exploration of People Living with Chronic Pain in Rural South Africa - Ramoshai, Tebatso (University of the Witwatersrand, Johannesburg, 2024)
Chronic pain is a highly prevalent global health concern. While much research has been conducted on the prevalence, treatment, and management of chronic pain, few studies have explored the experiences of people living with chronic pain, particularly in the South African context. This study aimed to explore and interpret how HIV-negative people living with chronic pain perceive their personal experiences with chronic pain and the impact it has on their lives. Part of a larger study that investigated the factors that influence the experience, daily activity, and disclosure of pain in people living with and without HIV in rural South Africa, this study conducted a qualitative exploration and interpretation of pre-collected interview data on a purposively selected sample of 16 HIV-negative individuals living with chronic pain from the Limpopo province of South Africa. Thematic analysis was used to analyse the data. Seven main themes emerged from the data: The nature of pain, participants’ typical physical activity, pain interference, disclosure of chronic pain, reactions to pain disclosure, benefits of disclosing pain, and social support. The findings suggest that for HIV-negative people living with chronic pain, the impact of pain is multidimensional. All participants experienced pain interferences; however, there was little to no difference in participants' physical activity levels regardless of interferences. The findings suggest that economic stressors may be an influential factor in how pain is experienced between any two pain cohorts, determining whether there will be a change in physical activity levels or not. Furthermore, contrary to previous concerns in a South African cohort with chronic pain, pain disclosure was high in this cohort; therefore, participants were able to recruit different types of social support from close others. This research, therefore, contributes to the qualitative knowledge of the relationships between pain, physical activity, and the seeking of social support by people living with chronic pain in a South African context
A research report submitted in fulfillment of the requirements for the Master of Arts (Psychology), in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Chronic pain; Qualitative research; HIV-negative; South Africa; Disclosure; Non-disclosure; Social support recruitment; SDG-3: Good health and well-being